Detection of low permittivity floating plastic sheets at microwave frequencies - Costa, T. S. da.; Felício, J. M.; Vala, M.; Leonor, N.; Costa, J. R.; Marques, P.; Moreira, A. A.; Caldeirinha, R.; Matos, S. A.; Fernandes, C. A.; Fonseca, N. J. G.; de Maagt, P. (2023 17th European Conference on Antennas and Propagation (EuCAP), 2023)
Microwaves are surfacing in remote sensing as a viable or complementary technology to optical techniques for the detection and monitoring of floating plastic litter, given their advantages in, e.g., earth observation missions. There is a limited number of studies that analyze the detection of low permittivity plastics in a systematic manner. To contribute to this topic, we evaluated the microwave response of a few typical floating targets in two scenarios, one with near-static water and the other with waves. We present an interesting example of target in this paper, which involves very low amount of material - stretched and crumpled plastic sheets. The results, obtained for different transmit and receive polarization combinations, indicate a strong, distinct response of the plastic sheets, in both cases. The study shows that, at least under the tested conditions, microwave radar may be sensitive to very low amount of plastic, through an indirect detection process.